Effects of Coix seed extract, Lactobacillus paracasei K56, and their combination on the glycolipid metabolism in obese mice. Issue 3 (30th January 2023) - Zhang, Wei; Jia, Xiuzhen; Xu, Yuhan; Xie, Qiaoling; Zhu, Meizhen; Zhao, Zifu; Hao, Jingyu; Li, Haoqiu; Du, Jinrui; Liu, Yan; Liu, Wei‐Hsien; Ma, Xia; et al.
Abstract : Abstract: Coix seed extract (CSE) and probiotics have been reported to regulate glycolipid metabolism through different modes of action. We tested the effects of CSE, Lactobacillus paracasei K56, and their combination to determine whether they have synergistic effects on glycolipid metabolism of obese mice. We fed male C57BL/6J mice with high‐fat diet for 8 weeks to establish an obesity model. The obesity mice were selected and divided into five groups: the model control group and four intervention groups. After 10 weeks of continuous gavage intervention, the mice in the intervention groups exhibited lower body weight (lower about 2.31–4.41 g, vs. HFD 42.25 g, p  < 0.01), and epididymal (lower about 0.58–0.92 g, vs. HFD 2.50 g, p  < 0.01) and perirenal fat content (lower about 0.24–0.42 g, vs. HFD 0.88 g, p  < 0.05); decreased fasting blood glucose, total cholesterol, triglycerides, and VLDL; and increased HLDL, respiratory exchange ratio, energy expenditure, and amount of exercise performed. K56 + CSE‐combined intervention groups were more effective in lowering blood glucose, IL‐1β, and TNF‐α levels than the CSE and K56 alone interventions. The content of fatty acid synthase and SREBP‐1c protein in liver tissue was lower. The combination has synergistic effects on weight control, fat reduction, and blood glucose regulation by improving the chronic inflammatory state and reducing the content of lipid synthesis‐related enzymes of obese mice, which can hinder chronic disease progression. Practical Application: Coix seed extract can be used in obese people to regulate abnormal glucose and lipid metabolism and delay the development of chronic diseases.